2006
DOI: 10.1074/jbc.m602320200
|View full text |Cite
|
Sign up to set email alerts
|

The Replication Intermediates in Escherichia coli Are Not the Product of DNA Processing or Uracil Excision

Abstract: The current model of DNA replication in Escherichia coli postulates continuous synthesis of the leading strand, based on in vitro experiments with purified enzymes. In contrast, in vivo experiments in E. coli and its bacteriophages, in which maturation of replication intermediates was blocked, report discontinuous DNA synthesis of both the lagging and the leading strands. To address this discrepancy, we analyzed nascent DNA species from ThyA ؉ E. coli cells replicating their DNA in ligase-deficient conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 61 publications
2
49
0
Order By: Relevance
“…This issue has recently been re-addressed by Amado and Kuzminov, who, using a temperature-sensitive ligase mutant of E. coli, showed that essentially all newly synthesised DNA was synthesised in small pieces [17]. This strongly suggests that both leading and lagging strands can be synthesised discontinuously in vivo, contrary to accepted dogma, but supporting the original model [13].…”
mentioning
confidence: 51%
“…This issue has recently been re-addressed by Amado and Kuzminov, who, using a temperature-sensitive ligase mutant of E. coli, showed that essentially all newly synthesised DNA was synthesised in small pieces [17]. This strongly suggests that both leading and lagging strands can be synthesised discontinuously in vivo, contrary to accepted dogma, but supporting the original model [13].…”
mentioning
confidence: 51%
“…Next, we considered the possibility that base analogs are incorporated into the DNA of mutT mutants and are then excised, but this excision is somehow different from the excision in dut or rdgB mutants in that it does not cause chromosomal fragmentation. In dut mutant strains, the high level of uracil misincorporation combined with the efficient excision repair elevates the steady-state level of nicks in DNA (1,43,76). Nicks can be detected as relaxation of supercoiled plasmids.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, if uracil forms within DNA as a result of cytosine deamination (52), uracil DNA glycosylase (UDG), with the help of exonuclease III, acts to remove this base (50,75). Interestingly, UDG does not distinguish between the U · A base pairs (the products of uracil incorporation) and the U · G base pairs (the products of cytosine deamination), excising both uracils equally well (51,63), which leads to the elevated frequency of excision repair intermediates (nicks) in the dut mutants of E. coli (1,43,76).…”
mentioning
confidence: 99%
“…However, no uracil was detected in the bulk DNA of wild-type or dut-1 mutant cells (35), due to the presence of a highly active enzyme, UDG (42) (the product of the ung gene [17]). UDG excises every uracil-DNA almost as soon as it is incorporated; this excision generates the short replication intermediates in the dut mutants (1,74). In fact, it is the uracil excision that eventually kills, directly or indirectly, SL(dut) mutants, as all of them are known to be suppressed by ung inactivation (34,70,73).…”
Section: Vol 190 2008 Dut-dependent Mutants In E Coli 5843mentioning
confidence: 99%